A Retrospective Study of Success, Failure, and Time Needed to Perform Awake Intubation. Issue 6 (December 2016) - Joseph, Thomas T.; Gal, Jonathan S.; DeMaria, Samuel; Lin, Hung-Mo; Levine, Adam I.; Hyman, Jaime B.
Abstract : (Abstracted from Anesthesiology, 125:105–114, 2016) Although awake intubation is considered the "standard of care" when it comes to patients with difficult airways, anesthesiologists may shy away from the procedure because of concerns over complexity and length of time necessary for successful completion. The purpose of this study was to determine how long it typically takes to perform an awake intubation, as well as the procedure's effects on hemodynamics and what complications may arise as a result.